(untitled) (Global Journal of Management and Business Research, 2016)
The purpose of this research is to examine how the HRM practice affects on organizational performance in Banal Financial Banking Industry measuring the Labile Marketing Strategy in South Asisan Country, Bangladesh. It has been noted that there is a trend here in Bangladesh in financial & banking sector is establishing Islamic Banking with differentiate marketing strategy. This is why, in our research, we mainly focus to find-how HRM practice affects on Organizational Performance in Islamic & Conventional or Banal Banking Industry as banal financial banking industry in changeable marketing strategy of Bangladesh. We collected data from a large number of employees of 10 banks in Bangladesh to find the affiliation in between of human resource policy and organizational performance. As our main focus on banal financial banking industry measuring labile marketing strategy, we collected our data from 10 Islamic banks. The employees were from managerial & non managerial level of those banks. We use statistical analysis by using SPSS statistical software.